HTML and XHTML : interactive movie tutorials - McLeod, Scott; Carey, Patrick; Thomson Course Technology (Boston, MA. : Thomson Course Technology, 2006)
Movie tutorials in designing web page by using HTML and XHTML software. Includes glossary, quizzes and other information
A QuickTime for both Windows and Macintosh
Keywords: HTML (Document markup language).; Document markup languages